A review of the flatfish fisheries of the south Atlantic Ocean - Juan M. Díaz de Astarloa (Revista de Biología Marina y Oceanografía, 2002)
The flatfish fisheries of the South Atlantic Ocean are described from time series of landings between 1950 and 1998 and available information on species life history, fleets and gear characteristics, and economical importance of commercial species. In the southwest Atlantic, paralichthyid flounders, mostly Paralichthys patagonicus, P. orbignyanus and Xystreurys rasile are intensely exploited. While in southern Brazil, landings of these species reached a maximum of 1 892 t in 1989, in Argentina exceeded 10 000 t annually between 1989 and 1998. In the south-east Atlantic, the west coast sole, Austroglossus microlepis, and the Agulhas sole, A. pectoralis, although account for a minor percentage of the annual South African trawlfish catch, they are by far the most valuable fish per unit weight landed and are therefore the main target of the small trawlers. Landings of west coast sole peaked at nearly 2 000 t in 1972 but have declined steeply since then. Trawling is the most important method used in fishing for flatfish in the south-west Atlantic. Double-rig trawling, twin nets and entangling nets are employed for flatfish fishing. In the south-east Atlantic, the main flatfish catches are taken as by-catch in the demersal trawls fisheries. Flatfish represent a relatively small fraction of the total landings in both the south-west and south-east Atlantic, compared with other demersal fish species as hake.